Religious Education of Children in Interfaith Family - Mahsun; Mahmutarom; Ifada Retno Ekaningrum; Muh Syaifuddin; Yuldashev Azim Abdurakhmonovich (Program Studi Pendidikan Agama Islam (PAI), 2023)
The phenomenon of religious education for children born and raised in families with parents of different religions, Muslim and non-Muslim, is interesting to study. This field of qualitative research uses a phenomenological approach, aiming to describe the interaction of religion in interfaith families in the context of religious education in the family. Data collection took place from January to March 2023 for participants consisting of 10 families of different religions in Kaloran District, Temanggung Regency, Central Java Province. The results of the study show that there are three types of religious interaction in interfaith families. First, parents introduce all their religions to their children. Second, parents teach one religion to their children. Third, parents’ direct religion for their children based on division.